2022
DOI: 10.3390/ani13010041
|View full text |Cite
|
Sign up to set email alerts
|

Use of Heating Methods and Xylose to Increase Rumen Undegradable Protein of Alternative Protein Sources: 2) Cottonseed Meal

Abstract: The ruminal kinetics of protein sources may be changed by heat and sugar treatments. Thus, these processing methods may be used as alternatives to increase beef-cattle diets’ rumen undegradable protein (RUP). We aimed to evaluate the effects of processing cottonseed meals with autoclave, conventional, and microwave ovens, with and without using xylose, on the ruminal kinetics degradation parameters and intestinal digestibility (ID). In situ studies were conducted, and each sample was incubated in the rumen to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This improvement can be attributed to a decrease in the soluble protein component (a-value) and the c-value, resulting in an increased supply of RUP to the small intestine (Ahmad Khan et al, 2015). Molosse et al (2022) also observed alterations in the DM and CP kinetics of cottonseed meal and peanut meal (autoclave heated at 127°C), increasing both the b-value and RUP value. Moderate heat treatment (125°C) altered the chemical profile of the protein, resulting in the formation of cross-linkages and an increase in the C fraction of protein in rapeseed meal (Haese et al, 2022).…”
Section: Table 2: Kinetics Degradation Of Dry Matter In High Rdp-prot...mentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement can be attributed to a decrease in the soluble protein component (a-value) and the c-value, resulting in an increased supply of RUP to the small intestine (Ahmad Khan et al, 2015). Molosse et al (2022) also observed alterations in the DM and CP kinetics of cottonseed meal and peanut meal (autoclave heated at 127°C), increasing both the b-value and RUP value. Moderate heat treatment (125°C) altered the chemical profile of the protein, resulting in the formation of cross-linkages and an increase in the C fraction of protein in rapeseed meal (Haese et al, 2022).…”
Section: Table 2: Kinetics Degradation Of Dry Matter In High Rdp-prot...mentioning
confidence: 99%
“…In contrast, their EDCP values differed, suggesting that the heating method reduces degradation in the rumen but did not affect post-rumen-digestion. Post-ruminant digestion of cottonseed meal was increased after heating treatment (Molosse et al, 2022). The heating process altered the chemical profile of the protein, protein subfractions, rumen degradation, post-rumen digestibility, and protein structure (such as changes in the ratio of α-helix and β-sheet) (Ahmad Khan et al, 2015).…”
Section: In Vitro Digestibilitymentioning
confidence: 99%
“…Soybean, peanut, and cottonseed meals are the main protein sources used in feedlot cattle production in Brazil [7]. Although widely utilized, a significant portion of these feeds' protein is fermented in the rumen [8,9]. Thus, researchers have sought processing techniques (physical and chemical) to enhance protein protection against ruminal fermentation and improve protein utilization [10].…”
Section: Introductionmentioning
confidence: 99%